Improvement of the Strength-Ductility Balance in Ultrafast Heated Steels by Combining High-Temperature Annealing and Quenching and Partitioning Process - Castro-Cerda, F; Hernandez-Duran, E (Elsevier Ltd, 2021)
The microstructure and mechanical properties of an Fe-0.24C-1.4Mn-1.4Si steel were investigated after combining ultrafast heating (UFH) at a heating rate of 500 °C/s followed by fast cooling to room temperature (DQ) or quenching and partitioning processes (Q&P). Two peak temperatures were studied, annealing into the intercritical range and above the AC3 temperature. After ultrafast heating and quenching, the resulting microstructures revealed that intercritical annealing led to the formation of a banded ferritic-martensitic microstructure. On the other hand, heating above the intercritical range led to an even distribution of allotriomorphic ferrite grains upon fast cooling and a complex phase microstructure, consisting mainly of martensite, was produced. Q&P steel grades exhibit an enhanced mechanical behavior compared to their DQ counterparts, where yield strength, uniform elongation, and total elongation increased after partitioning at 400 °C. The ultimate tensile strength of the Q&P steels decreased compared to the DQ steels annealed at the same peak temperature. However, the final strength-ductility balance of the studied Q&P steels was superior to the DQ steel grades. Moreover, considerable strength and improved ductility were obtained through the combination of peak annealing above the AC3 temperature followed by Q&P. These results are attributed to an interplay between a sustainable TRIP effect and effective strain-stress partitioning among the microconstituents resulted after the Q&P process. © 2021 Elsevier B.V.